2006
DOI: 10.1128/mcb.26.9.3582-3594.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β Induces Rosettes of Podosomes in Primary Aortic Endothelial Cells

Abstract: Cytoskeletal rearrangements are central to endothelial cell physiology and are controlled by soluble factors, matrix proteins, cell-cell interactions, and mechanical forces. We previously reported that aortic endothelial cells can rearrange their cytoskeletons into complex actin-based structures called podosomes when a constitutively active mutant of Cdc42 is expressed. We now report that transforming growth factor beta (TGF-␤) promotes podosome formation in primary aortic endothelial cells. TGF-␤-induced podo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
152
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(176 citation statements)
references
References 62 publications
19
152
0
5
Order By: Relevance
“…Many podosomal components, such as cortactin, focal adhesion kinase or vinculin are Src substrates. Consequently, pharmacological agents targeting Src activity affect podosome formation (Linder et al, 2000;Tatin et al, 2006;Varon et al, 2006). Indeed, consistent with previous reports, NaF-induced podosomes were found to be sensitive to PP1.…”
Section: Discussionsupporting
confidence: 78%
“…Many podosomal components, such as cortactin, focal adhesion kinase or vinculin are Src substrates. Consequently, pharmacological agents targeting Src activity affect podosome formation (Linder et al, 2000;Tatin et al, 2006;Varon et al, 2006). Indeed, consistent with previous reports, NaF-induced podosomes were found to be sensitive to PP1.…”
Section: Discussionsupporting
confidence: 78%
“…It was recently shown that SRC-induced podosomes in human umbilical vein endothelial cells display gelatinolytic activity due to MMP2, activated by MT1-MMP (67). In addition, when formation of podosomes was compromised by addition of PP2, an inhibitor of Src as well as podosome formation, MT1-MMP-driven matrix degradation was inhibited, suggesting that SRC kinase is an upstream regulator of MT1-MMP-dependent matrix degradation in podosomes (68). The current data provide support for a mechanistic link between collagen adhesion, integrin clustering, and integrinmediated signaling via Src kinases to induce expression of EGR1, resulting in transcriptional activation of the MT1-MMP promoter and subsequent MT1-MMP-catalyzed intra-peritoneal invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a number of proteins that are important for invadopodia formation and for the execution of EMT have been identified, strongly suggesting that invadopodia formation could be involved in EMT-driven cell invasion. Both EMT and invadopodia formation can be stimulated by various growth factors, including EGF, HGF, PDGF, and TGFβ [5,197,221]. The engagement of these growth factors leads to the activation of the non-receptor tyrosine kinase Src.…”
Section: Invadopodia and Their Role In Emtmentioning
confidence: 99%